Designing a recombinant Bacmid construct of HCV core+1 in Baculovirus expression system - Safarnezhad Tameshkel, Fahimeh (Iran J Microbiol, 2015)
BACKGROUND AND OBJECTIVES: Hepatitis C virus (HCV) chronically infects around 200 million people worldwide and frequently causes liver cirrhosis and hepatocellular carcinoma. Rapid detection of this virus results in decreasing the distance between infection and initiation the anti-viral treatment, and may prevent most of the undesirable consequences. The new detected HCV protein “Core+1” made from the ribosomal frame shift in Core region is an important candidate for diagnostic tools. This study was conducted to design a recombinant Bacmid plasmid expressing the HCV 1a Core+1 sequence in the Baculovirus expression system for further diagnostic applications. MATERIALS AND METHODS: The HCV Core +1 gene was amplified by PCR using the pcDNA-HAF recombinant vector that contained the Core+1 sequence from HCV genotype 1a as a template, and the specific primers with 2 restriction sites for Nco I and Xba I restriction enzymes. The PCR product was cloned in XbaI/NcoI restriction sites of the linearized pFastBac-HTB vector and evaluated by using those restriction enzymes and sequencing. Then the recombinant pFastBac-HTB vector was transformed in DH10Bac and the result was screened and confirmed by X-Gal discrimination and PCR. RESULTS: The HCV 1a Core+1 was successfully amplified and the PCR product was confirmed by using the related restriction enzymes and sequencing. Cloning of pFastBac vector with the purified PCR product of HCV Core+1 was confirmed. Finally, the recombinant Bacmid was successfully transformed in DH10Bac. CONCLUSION: The recombinant Bac-Core+1 expression vector is considered as an important tool to transfect the sf9 cell line and expression the Core+1 protein.